2018
DOI: 10.1002/jnr.24269
|View full text |Cite
|
Sign up to set email alerts
|

The opioid system and the social brain: implications for depression and suicide

Abstract: In the past decade, considerable attention has been drawn to social interactions and behaviors as sources of pleasurable (social reward) and painful (social pain) emotional states. While the role of the opioid system in the regulation of reward and pain processes has long been recognized, it has more recently been investigated and characterized in the specific context of social experiences across several mammalian species. Accordingly, the present narrative review provides a comprehensive summary of studies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 145 publications
2
22
0
Order By: Relevance
“…Results showed a specific increase in the expression of GNAI2 in depressed individuals. Because Importantly, these findings appear consistent with imaging studies published over the last 15 years (see [37] for review), mostly conducted using positron emission tomography (PET) and the MOR selective radiotracer [ 11 C]-Carfentanil. These studies first indicated that acute emotionally salient stimuli (whether the recall of sad autobiographical events [4], exposure to social rejection [7], or viewing pictures of appetizing food [38]) led in heathy volunteers and depressed individuals [8] to rapid changes in MOR availability, notably at the level of the AI, reflecting the well-characterized notion that MOR activity modulates hedonic tone.…”
Section: Discussionsupporting
confidence: 85%
“…Results showed a specific increase in the expression of GNAI2 in depressed individuals. Because Importantly, these findings appear consistent with imaging studies published over the last 15 years (see [37] for review), mostly conducted using positron emission tomography (PET) and the MOR selective radiotracer [ 11 C]-Carfentanil. These studies first indicated that acute emotionally salient stimuli (whether the recall of sad autobiographical events [4], exposure to social rejection [7], or viewing pictures of appetizing food [38]) led in heathy volunteers and depressed individuals [8] to rapid changes in MOR availability, notably at the level of the AI, reflecting the well-characterized notion that MOR activity modulates hedonic tone.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, a 3-day study of men with depression and opioid use disorder also demonstrated decreases in suicidal ideation after a large dose of sub-lingual buprenorphine, although this trial was not placebo controlled 329 . Larger studies are needed to replicate the finding that opioids may improve suicidal ideation, and this is an observation that comports with the hypothesis that psychic pain is an important determinant of suicide risk 330 .…”
Section: [H3] Safety Planning Intervention or Crisis Response Planninmentioning
confidence: 92%
“…Such dysregulation could in turn play an important role in psychopathologies such as PTSD, depression or (social) anxiety. These psychopathologies are related to hyper-reactivity of neural networks linked to social rejection and decreased reward responsivity (Lutz et al, 2018;Lutz and Kieffer, 2013a;Ribeiro et al, 2005). Similarly chronic opioid use can result in anhedonia and deficits in emotion regulation (Garland et al, 2019(Garland et al, , 2017.…”
Section: Fear and Stressmentioning
confidence: 99%
“…As previously mentioned, this response is highly adaptive allowing the individual to regulate their social pain and subsequent behavior to create new opportunities for positive social experiences (Fig 1A). The experience of traumatic events or continuous exposure to stress however, leads to a chronic dysregulation of the MOR system resulting in less responsivity to social reward and hypersensitivity to threat, both of these characteristics are strongly associated with social anxiety and depression (Garland et al, 2019;Lutz et al, 2018;Lutz and Kieffer, 2013b;Shurman et al, 2010). Thus, on the biopsychological and behavioral level, the individual enters a self-sustaining negative feedback loop with a strong bias toward anticipation of negative social cues.…”
Section: A Mu-opioid Feedback Model Of Social Interactionmentioning
confidence: 99%